Efecto del hidrogel y biochar sobre el crecimiento temprano del maíz (Zea mayz) bajo limitación hídrica - Marín Valdez, María Elisabeth (2022)
The present investigation was carried out in the nursery area of the Escuela Superior Politécnica Agropecuaria de Manabí "Manuel Félix López", with the objective of evaluating the effect of hydrogel and biochar on the early growth of corn (Zea mays.) under water limitation. The experiment was carried out for a period of 24 days and the planting was done in containers (pots), a complete random design (DCA) was used, with six treatments, four replications and 24 experimental units. The doses evaluated were two doses of hydrogel (0.50 and 1 g/plant) and two doses of biochar (25 and 50 g/plant). The recorded variables were stem diameter, leaf area, plant dry weight and root dry weight at 12 and 24 days after sowing. Data were subjected to analysis of variance (ANOVA) and separation of means with Tukey's test at 5% error probabilities. The results showed that treatment T6 (with irrigation and without hydrogel or biochar) was the one that obtained the best results compared to the other treatments. However, the treatments that contained hydrogel and biochar, T4 with (1g of H and 50g of Bi), compared to the treatments (T1, T2, T3 and T5), was the one that achieved the best results in all the variables evaluated. Soil moisture data were taken daily with the instrument (Soil Moisture Kit), the treatment with irrigation and without hydrogel (T6) obtained better results compared to the other treatments that contained hydrogel and biochar.